Myelin oligodendrocyte glycoprotein (MOG)-IgG associated optic neuritis as a new issue in the differential diagnosis of optic neuropathy - Nowacka, Barbara; Lubiński, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
Myelin oligodendrocyte glycoprotein (MOG)-IgG associated optic neuritis has been established as a new subset of optic neuropathy. The recent development of serological diagnostics of MOG-IgG has improved our ability to identify this disease, which differs from multiple sclerosis and aquaporin 4 (AQP4)-IgG positive neuromyelitis optica spectrum disorder in terms of clinical features and treatment outcomes. Based on available literature, we summarize the current knowledge of the clinical presentation, evaluation and management of patients with MOG-IgG associated optic neuritis, with a comparison to the other most common types of optic neuritis.